Evaluasi pendidikan staf dan kepemimpinan kepolisian tingkat pertama di Indonesia menggunakan model Kirkpatrick - Eko Wirawan; Nurhattati Fuad; Matin Matin (Universitas Pendidikan Indonesia, 2026)
Police leadership education is a substantial investment, yet its effectiveness is seldom evaluated beyond participant satisfaction, and evidence on tiered police managerial education remains scarce. This study evaluates Indonesia's First-Level Staff and Leadership School (Sespimma) using Kirkpatrick's four-level model, aiming to assess reaction, learning, behavior, and results, and to identify the factors that enable and hinder the application of the education. It adopts a qualitative, multi-source case study. An in-depth interview with an alumnus, together with observation and performance documents (LAKIP and IKU), was coded thematically in ATLAS.ti 24 using deductive and inductive coding; open-ended questionnaire responses from sixteen alumni and two supervisors were analyzed as summarized themes, while closed Likert items were reported descriptively as supplementary context. The analysis produced twenty-seven codes across the four levels plus enabling and hindering factors and recommendations. Findings show a positive reaction; gains in management knowledge and in leadership, communication, and problem-solving skills; transfer of learning into more systematic managerial practice; and organizational benefits perceived by supervisors, while subordinate readiness and organizational culture condition transfer.